Kepuasan Konsumen Pengukuran Indeks Kepuasan Konsumen di Puskesmas Dago Bandung - Jutika Cahyana, Babay; Rina Rostarina (Institut Sains dan Teknologi Al-Kamal, 2022)
PUSKESMAS, Is a Public health center, which is the primary health service facility for the local government, is required to provide the best possible service for the surrounding community who need health services. Measuring customer satisfaction is done by using the Importance Performance Analysis (IPA) method. In this method, it is necessary to measure the level of conformity to find out how much the customer is satisfied with the company's performance, and how much the service provider understands what the customer wants for the services they provide. In the Importance-Performance Analysis, mapping is carried out into 4 quadrants for all variables that affect service quality. Quadrant divisions in Importance-Performance Analysis are categorized on the X-axis Very Unsatisfactory to Very Satisfying, and the Y-axis Very Unimportant to Very Important. The study was conducted on 31 consumers of the Dago Health Center in Bandung, which aimed to determine customer satisfaction with the services provided by the Puskesmas. There are five factors measured, the quality of service facilities, reliability, responsiveness, confidence, and empathy. The results are then calculated using the Customer Satisfaction Index, and Importance Performance Analysis. The results of testing the validity and reality, resulted in all questionnaire points and respondents declared valid and reliable. The results of the analysis of the average value of expectations and customer satisfaction can be seen that the quality of service facilities, quality of service reliability, quality of service responsiveness, quality of service confidence, quality of service empathy, has an achievement or work performance above 90%. This means that the Dago Health Center in Bandung City has succeeded in fulfilling the desires or satisfying consumers, in fact, the Quality of Service Confidence item has a value of 101% this means that the consumer's belief service exceeds the expectations of consumers. The results of the analysis of the expectation and performance matrices, where the quality of service facilities, service reliability quality, service responsiveness quality, service assurance quality, service empathy quality. The five criteria are in quadrant I, which means that the Dago Health Center is in the strategy to maintain the achievements that have now been achieved, because the five criteria for services provided have met consumer expectations.